(untitled) (Poornaprajna International Journal of Management, Education & Social Science (PIJMESS), 2025)
Purpose: This study investigates how Zero-Based Budgeting (ZBB) can optimize cost management strategies and enhance financial planning across various industries. Methods: A secondary data analysis was conducted using financial reports and empirical studies from 2020 to 2024 to evaluate the effectiveness of ZBB. Findings: ZBB implementation led to significant cost reductions, with savings rising from 2.5M (3%) in 2020 to 7.5M (9%) in 2024. Operational expense reductions improved from 4% to 10%. A strong positive correlation (r = 0.96) was observed between ZBB adoption and financial planning efficiency, increasing from 68% to 82%. Regression analysis (β = 0.33, p = 0.163) suggested that structured financial planning through ZBB positively influences revenue growth. Challenges include administrative complexity and short-term cost-cutting risks. Value: The study highlights the strategic role of ZBB in cost management and financial sustainability, recommending AI-driven budgeting tools, pilot program rollouts, and industry-specific customization to maximize effectiveness. Type of Research: Empirical Research using secondary data.